Nature of the private hospital services toward universal health coverage: A systematic scoping review of the developing countries evidence - Razieh Fallah; Mohammadreza Maleki (Wolters Kluwer Medknow Publications, 2021)
Private hospital services (PHS) with the undeniable effects on the Universal Health Coverage (UHC) goals have a considerable contribution to the health system of developing countries. The purpose of this systematic scoping review (ScR) was to identify and map the available evidence regarding the developing countries to scrutinize the nature of the PHS toward UHC through providing graphical/tabular information of the records trends and types, sources of the records, frequent settings, drivers of the PHS growth, range of the PHS, behaviors of the PHS, and opportunities for policy actions. This study was performed following the 2017 published methodological guidance of the Joanna Briggs Institute for the conduct of ScR. Furthermore, a narrative-thematic synthesis integrated with the systematic analysis applying approach to health system strengthening (HSS) through systems thinking was employed. Thirty-two included records in English that met the inclusion criteria were found between 2011 and July 2020. There has been a sharp increase in the generation of the records with a 90.6% growth rate between 2015 and 2020. The most frequent records types were review article, and the lancet was the most specialized journal. India was the most frequent country. Near half of the growth drivers of PHS have been originated from the governance. Besides, the range of PHS was identified only about Mongolia, and the significant frequency of codes of the PHS behaviors (32.6%) was related to integrated people-centered health service delivery. 47.8% of the identified HSS interventions were recommended about governance. Governance plays a decisive role in the nature of the PHS in UHC. Concerning the dynamic architectures of interactions between health system functions, probably the countries themselves have realized the importance of the governance role in the HSS than other functions. Given the all of the recommended interventions were a combination of foundational and institutional, sustainable participation of PHS in the health system seems far and requires a solid will of the governments. Future research is needed about the range of PHS and its behaviors in terms of consumables, revenue-raising, and pooling of funds.